From Leukocoria to Orbital Retinoblastoma: Consequences of Delayed Treatment in a 3-Year-Old Child - Eva Imelda; Sarra Mutiara Adev; Navneet Shamsundar Toshniwa (Heca Sentra Analitika, 2026)
Retinoblastoma is the most common primary intraocular malignancy of childhood, and delayed treatment can shift management from globe preservation to survival-oriented intervention. We report a 3-year-and-4-month-old girl with bilateral advanced retinoblastoma who re-presented after an 18-month default from recommended treatment. She had progressive left-eye proptosis and severe cancer-related cachexia, weighing 9.2 kg, below the 3rd percentile for age. She had initially been evaluated at 1 year of age for bilateral leukocoria, when urgent enucleation was advised but declined by caregivers. On re-presentation, contrast-enhanced CT of the brain and orbits showed a 24 × 18 mm retrobulbar soft-tissue mass surrounding a collapsed left globe. At the same time, the right eye contained an advanced calcified intraocular tumor filling the vitreous cavity, consistent with ICRB Group E disease. Systemic staging confirmed locoregionally confined disease. The patient received four cycles of neoadjuvant pediatric VEC chemotherapy. Subsequent assessment showed no light perception in either eye, tumor- and chemotherapy-induced phthisis bulbi in the left eye, and an unsalvageable Group E tumor in the right eye. Because severe malnutrition and systemic frailty made simultaneous bilateral surgery high risk, sequential bilateral enucleations were performed under general anesthesia with a four-week interval to optimize physiological recovery. Histopathology confirmed poorly differentiated bilateral retinoblastoma, with transmural scleral invasion in the left eye and massive choroidal invasion in the right eye; both elongated optic nerve margins were tumor-free. Dermis-fat graft reconstruction was not feasible due to the absence of subcutaneous adipose tissue. At 6 months, the sockets were stable with no clinical or radiological recurrence. This case highlights the consequences of treatment delay and supports individualized staged enucleation in fragile pediatric patients.